Vision loss caused by immunoglobulin G4–related disease of the skull base complicated by a mucocele of the sphenoid sinus. Issue 9 (27th March 2022) - Detiger, Sanne E.; Paridaens, Dion; Verdijk, Robert M.; van Laar, Jan A.M.; Dammers, Ruben; Monserez, Dominiek A.; Nagtegaal, A. Paul
Abstract: Background: Immunoglobulin G4‐related disease (IgG4‐RD) is a fibro‐inflammatory disorder and manifestation in de paranasal and sphenoid sinus is well recognized. In this patient, IgG4‐RD presented in an unusual manner with vision loss due to mucocele formation in the sphenoid sinus. Case Description: A 19‐year‐old man, with an unremarkable medical history, was referred with decreased vision in the left eye, headaches, and a sharp pain in the left orbit and ear. Compression of the left optic nerve due to a large mucocele caused papillary edema and emergency endoscopic marsupialization of the mucocele was performed. When the vision decreased again, a more extensive decompressing sphenoidotomy was performed. Histopathology showed IgG4‐RD. Despite dexamethasone, the lesion expanded to the anterior skull base and the patient required repeat endoscopic surgery. After 3 months, a decrease in smell and vision warranted for a fourth extensive endoscopic decompressing surgery, complicated by a cerebrospinal fluid leak. Prednisone and later rituximab were commenced. Unfortunately, the patient reported a complete loss of vision after 4 months of rituximab due to increased mass effect on the optic nerve. An extensive combined craniofacial‐endoscopic surgery was performed to remove the entire mucocele and to prevent further contralateral and intracranial progression. Methylprednisolone monthly was commenced to prevent further complications. Discussion: This case illustrates that in therapy‐resistant sino‐orbital IgG4‐RD, extensive surgery might be necessary at an earlier stage. It may even be the only option to prevent irreversible damage to the surrounding tissues. A multidisciplinary approach in the management of sino‐orbital IgG4‐RD is therefore warranted.